New distributional records of the exotic land snail Bradybaena similaris (Férussac, 1822) (Gastropoda, Bradybaenidae) in Argentina - Serniotti, Enzo Noel (2019)
Bradybaena similaris (Férussac, 1822) is an invasive land snail species native to East Asia, which is widely distributed in South America, including Argentina, Brazil, Colombia, Uruguay and Paraguay. In Argentina, very few previous records coming from the Tucumán and Misiones Provinces are available for the species. In this work, we report new occurrences of B. similaris in the country from Misiones Province, and include the southernmost record for the species in South America from Entre Ríos Province. We used shell morphology, morphological features of the reproductive system and radulae, and DNA sequences from 16S-rRNA gene for species-specific identification. These new distribution data reaffirm the need to monitor the southern dispersion of invasive snails in South America, especially those causing damage to several crop species.